KARAPASAN DAN KASITURUSAN: PERAN TRADISI LISAN DALAM UPAYA MENJAGA RELASI MASYARAKAT LINTAS IMAN DI TANA TORAJA - Welem, Theofilus (Pusat Riset Manuskrip, Literatur, dan Tradisi Lisan, 2023)
The knowledge of oral tradition as a local wisdom in Toraja society today is starting to decrease. Gradually, it is being displaced by the knowledge and teachings of religions such as Christianity and through modern knowledge. This problem is certainly something that needs to be addressed. Efforts are needed to remind Toraja people about their oral traditions so that they are not lost or forgotten. With this effort, it is hoped that oral traditions can continue to be practiced in the context of the life of Toraja people who are plural in terms of beliefs. This paper focuses on building a construction of local theology based on oral tradition, namely through Karapasan (peace/harmony) and Kasiturusan (community participation) in an effort to maintain interfaith community relations in Toraja. The research method used is qualitative method and Clemens Sedmark's theory of local theology. The results obtained show that Karapasan and Kasiturusan contain values of peace, unity, tranquility, mutual attention, and mutual cooperation. The oral tradition can be a building of local theology that needs to be kept in mind and practiced in the journey of life of the people of Tana Toraja in the midst of various different belief backgrounds. In the end, a good and close relationship between one another is maintained.